BITLIS ON THE INSPECTIONAL REPORTS OF CHP(1939-1945) - Uğur ÜÇÜNCÜ (Fırat University, 2020)
The CHP Inspectorate established to provide control over the Party organization and to strengthen the centralized structure of the Party. The Party Inspectors were appointed from the region and from different region deputies or Party members. Inspectors sent detailed reports and prepared for their travels, observations and investigations to the General Secretariat of the CHP. One of the CHP Inspectorate regions included Bitlis, Mus, Van and Siirt. Therefore, the Party inspectors also made the inspections in Bitlis and sent their reports including their findings and suggestions to the CHP General Secretariat. One of these reports was prepared by Tevfik Temelli and Ahmet Süreyya Örgeevren of Bitlis deputies in 1940. This report revealed the judicial, sanitary, social and administrative problems of Bitlis and its districts and it suggested solutions to these problems. The second 71-page report was prepared by Tokat Deputy Hasip A. Aytuna about Bitlis, Siirt, Muş and Van in 1943 is very valuable. This report has information, observations, determinations and evaluations about the roads, people's language, social life, tribes, immigrants and immigration roads, public order, gendarmerie, judiciary, civilian authorities, officers as well as health, agriculture, education, trade, economics, CHP and Community Center Organizations of Bitlis. The reports of CHP Mus Region Inspector Erzincan Deputy Fevzi Kalfagil are also striking. The last reports provide invaluable information about the geography, population, economy, socio-cultural life of the Bitlis and its districts: namely Ahlat, Tatvan, Mutki and Hizan in 1945. This study will reveal the general situation of Bitlis and its surroundings according to CHP inspection reports of 1939-1945 during the World War II. It will also demonstrate the approach of the Single Party Government.